Fenomena Jual Beli Voucher Live Streaming dari Shopee Perspektif Fikih Muamalah - Khaliq, Muzayyanah (Program Studi Hukum Ekonomi Syariah, 2024)
In era millennials, looking at development statistics data Which very fast happen in every e-commerce one of them is Shopee. Shopee provider feature is live now present with discount voucher prize by 20% up for 50.000 if watch the live. Even the voucher can we get it maximum 5 vouchers in one sunday and maximum 1 voucher each in the evening, from 20.00 WIB to 00.00 WIB. Then with initiative Shopee user, the voucher traded with price 7000 by voucher buyers sending a live streaming product link to the voucher owner (non-seller) who has claimed the live voucher, then the voucher owner clicks on the link and not forget choose product as well as sent on voucher buyers. The aim of the research about respond sell buy live streaming vouchers from Shopee to find out the contracts and laws contained in buying and selling transactions for live Shopee vouchers using mu'amalah jurisprudence analysis. The methodology used in the research is qualitative by looking at documentary materials, magazines, journals and newspapers. The emphasis of library research is to find various theories, laws, postulates, principles, opinions, ideas and so on. Based on the results of the author's analysis, buying and selling vouchers is a fake sale and purchase contract for benefits because mabī' (goods being sold) is not last a long time (ghairu ta'bīd). This matter causing buying and selling to be haram even if the 'aqidain are mutually willing.